Novel X-Ray and Optical Diagnostics for Studying Energetic Materials: A Review. (September 2020) - Zhang, Yiyang; Chen, Sen; Cai, Yang; Lu, Lei; Fan, Duan; Shi, Jinchun; Huang, Junyu; Luo, Sheng-Nian
Abstract: Thermomechanical, physical, and chemical processes in energetic materials (EMs) during manufacturing and processing or under external stimuli such as shock compression, involve multiple temporal and spatial scales. Discovering novel phenomena, acquiring new data, and understanding underlying mechanisms all require temporally and spatially resolved diagnostics. Here, we present a brief review of novel diagnostics that are either emerging or have existed but rarely been applied to EMs, including two-dimensional (2D) and three-dimensional (3D) X-ray imaging, X-ray diffraction, coherent X-ray diffraction imaging, small angle X-ray scattering, terahertz and optical absorption/emission spectroscopy, and one-dimensional (1D) and 2D laser-based velocity/displacement interferometry. Typical spatial scales involved are lattice (nanometer and micrometer) and typical temporal scales (femtosecond, picosecond, nanosecond, microsecond, and millisecond). The targeted scientific questions and engineering problems include defects, strengths, deformations, hot spots, phase changes, reactions, and shock sensitivities. Basic principles of measurement and data analysis, and illustrative examples of these are presented. Advanced measurements and experimental complexities also necessitate further development in corresponding data analysis and interpretation methodologies, and multiscale modeling.